“SELF” IN THE SYSTEM OF COLLECTIVE ACTION OF SOCIAL INTERNET NETWORKS: SOCIO-PHILOSOPHICAL ASPECT - Polishchuk, Olexander; Polishchuk, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The modern period is marked by the invention of the Internet, providing conditions for the emergence of social networks. Thanks to the Internet, the number of communications are growing, the means of transmission are constantly simplifying, becoming compact and accessible. This is due to both the rapid technical-technological achievements, and COVID-19 pandemic situation forced people to reformat their relations and move from face-to-face interaction to the virtual one. Transformational changes have involved the formation of the self, as well as the collective action. The aim and tasks are to study the possibilities of social Internet networks in the formation of “self” and his involvement in the system of the collective action. Research methods include an interdisciplinary approach: social-scientific and philosophical directions. Their alternation, the most effective for such a problem, is combined with the dialectical, hermeneutic, and phenomenological methods. Research results. Ensuring the productivity of conclusions is guaranteed by the successful selection of the scientific literature, but, above all, on the methodology used in its analysis and study of the real state of affairs. The objective reality as the object of the research, on the one hand, appears to be real, on the other hand, man’s interpretations. However, in both cases it is about the adequacy of reading, strict translation into the mode of structuring the theory, conclusion, and forecasting regarding certain aspects, such as the description of the current state formation of “self” and his involvement in the system of the collective action based on social Internet networks and characteristics of potential dangers in the terminology of Information society. Discussion. The study of the virtual world, which is directly related to the development of information technologies has gained philosophical understanding in the works of D. Bell, M. Castells, N. Krylova, E. Toffler and others. The multifaceted nature of this phenomenon is studied in the concepts of foreign scientists, in particular V. Afanasiev, A. Voronov, A. Kroker and M. Nosov. In Ukrainian science, V. Andrushchenko, M. Boichenko, I. Devterov, V. Kremen, V. Liakh, B. Sivirynov, and others studied the socio-philosophical aspects of virtualization and informatization of society. The problem of Internet addiction has been studied by such foreign researchers as A. Voiskunskyi, A. Zehorov, and K. Young. Among Ukrainian researchers, there are works of N. Buhaiova and L. Yurieva. Network interaction of individuals is carried out with the help of social Internet networks. The modern theory of social networks dates back to the middle of the XX c. thanks to the works of R. Solomonoff and A. Rapoport. The term “social network” was first used in 1954 by the sociologist J. Barnes in his work “Human Relations”, which also presented several sociograms - visual diagrams in which each person looked like a dot, and the lines between them indicated their relationships. Later, P. Erdos, A. Rainier, D. Watts and S. Strohach developed the theory of social networks, exploring the principles of joining individuals into groups, the degrees of the closeness of heterogeneous groups in terms of sociological and mathematical methods. Analyzing “The Strength of Weak Ties” – that’s what the article was called M. Granovetter pointed out the paradoxical possibilities that the network guarantees. The boundaries of strong ties (a family, a circle of friends, etc.) are too dense for further growth; and weak ties, which include a wider circle of acquaintances (those, in turn, are also included in other conditional circles of communication and interaction), are quite sparse, which is more promising in terms of growth and access to a variety of resources: information, intellectual, financial and others. Also, this topic is represented in the works of J. Barlow, R. Barbrook, E. Cameron, N. Christakis, J. Fowler, J. Heitzman, P. Taylor and others. Соnclusion. As we can see, the network interaction of individuals and its influence on the formation of “self” is of great interest to researchers, especially in the period of information development of the society. After all, it is the information that encodes the value social load contributes to the formation of “self” and his involvement in the system of collective action and promotes the processes of identification in the virtual world. However, these issues are still poorly studied today, and therefore the features of the involvement of “self” in the system of collective action through network, interaction are relevant and promising, especially in terms of axiological and epistemological approaches.